2017
DOI: 10.5897/ijnm2017.0283
|View full text |Cite
|
Sign up to set email alerts
|

Pain as 5th vital sign: impact of pain assessment training program on Nigerian nurses knowledge of pain management

Abstract: Pain is subjective and it can only be described by the individual experiencing it. It is the main reason why people seek medical help. Nurses play a major role in the management of pain; hence they must be highly knowledgeable to ensure their practices are of high quality. The aim of this study was to evaluate the impact of Nurses' Pain Educational Program (NPEP) on nurses' knowledge of pain management. The quantitative design was employed in the study; five lectures on the Nurses Pain Educational Program (NPE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
1
2
1
Order By: Relevance
“…It could be possible that the nurses in the study by Zeb and colleagues (2019) did not use the information they acquired. This finding also disagrees with earlier studies by Chou and Colleagues (2016) in Asia and Onianwa et al (2017) in Nigeria that showed that some nurses do not have the competency required in pain management practice. For instance, Chou and Colleagues (2016) suggest that nurses need to acquire relevant information pertaining to pain management for optimum care delivery, while Onianwa et al (2017) found that nurses were deficient in their baseline pain management knowledge.…”
Section: Discussion Of Findingscontrasting
confidence: 99%
See 1 more Smart Citation
“…It could be possible that the nurses in the study by Zeb and colleagues (2019) did not use the information they acquired. This finding also disagrees with earlier studies by Chou and Colleagues (2016) in Asia and Onianwa et al (2017) in Nigeria that showed that some nurses do not have the competency required in pain management practice. For instance, Chou and Colleagues (2016) suggest that nurses need to acquire relevant information pertaining to pain management for optimum care delivery, while Onianwa et al (2017) found that nurses were deficient in their baseline pain management knowledge.…”
Section: Discussion Of Findingscontrasting
confidence: 99%
“…Other studies in Nigeria by Onianwa, Alonge, Otegbayo, Ike, Chukura, Akanbi et al (2017) and Nwagwu and Oshiname (2009) found that nurses and other health care professionals can obtain information related to pain management through the process of patient assessment. This is necessary because it would guide the nurse in appropriate decision about administration of analgesics.…”
Section: Research Hypothesesmentioning
confidence: 98%
“…In our study about 16(4.4%), anti-pain side effects were documented and the most reported side effect was Nausea and vomiting (13(3.6%). This finding is almost similar to the study done in Niger [ 38 ].…”
Section: Discussionsupporting
confidence: 92%
“…Evidences from developed countries like USA, UK, Australia, Malaysia, India, and New Zealand show that effective pain relief during the post-operative period was problematic (Chou et al, 2016;Rababa, 2018;Stodart & McCallum, 2014;Subramanian et al, 2017). Similar reports of disappointment with pain relief are equally available in Africa and Nigeria in particular (Githemo, Karani, Ogutu & Gachoka, 2018;Onianwa, et al, (2017). Masigati and Chilonga (2014) studied post-operative pain management outcome in Tanzania and found that only 18 (14.5%) reported absence of pain at rest during the early post-operative period.…”
Section: Introductionmentioning
confidence: 99%